ANALISIS KOMPERATIF PENDAPAT IBN HAZM DAN IMAM SYAFI’I TENTANG TALLAQ MUALLAQ - Elyanur, Elyanur (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, Ekonomi Islam, 2017)
Talaq mu'allaq is a divorce that is effected by a matter or a time when the condition mentioned in the talak which is pronounced by the true husband occurs. When the talaq occurs, the relationship between the husband and wife was broken off. In this article the author discusses three existing problems; One, Ibn Hazm's opinion of talak mu'allaq in his book, Al-Muhalla that rejected the validity of talaq mu?allaq. Secondly, Ibn Hazm's method of law elicitation on the issue of talak Mu'allaq which only refers to the argumentation from Qur'anic verse by just looking to its meaning without considering the interpretation of the verses. He ignored the interpretation in detail and rejected the qiyas in the affairs of religion so that any problems related to his Islamic laws strongly prohibited the use of qiyas / logic. Third, about the indication of differences of opinion between the two, that is what distinguishes between Imam Shafi'i's opinion with Ibn Hazm itself is that of different ways of governing the law.